Perlindungan Hukum Lisensi Hak Cipta Lagu dan Musik Daerah Berdasarkan Undang-Undang Nomor 28 Tahun 2014 Tentang Hak Cipta Dan Konvensi Bern: Legal Protection of Copyright Licences for Regional Songs and Music Based on Law Number 28 of 2014 Concerning Copyright and the Bern Convention - Widyanti, Yenny Eta (WARKAT, 2023)
This paper analyzes legal issues regarding the legal protection for folk song and music licenses in Indonesia. Indonesia which has cultural diversity is expressed through several folk songs whose creators are anonymous, so they are very susceptible to being changed, re-performed in a way that is inconsistent with the values ​​that live in society and even claimed by irresponsible foreigners. This research is a normative legal research, using a statutory approach. Based on primary and secondary legal materials, then the results of the research show that the copyright of folk songs and music is a protected object in article 40 of Law Number 28 of 2014 concerning Copyright (Copyright Law), and folk songs and music whose creators are anonymous is regulated in Article 38 and Article 39 of Copyright Law. In the Berne Convention folk songs and music whose authors are anonymous are protected in Article 15 Paragraph (4.a) which regulates the protection of unpublished works, and anonymous authors from participating countries of the Berne Convention.